Testing The Antibacterial Activitiy of A Facial Wash Preparation of Sweet Belimbing Leaf Extract (Averrhoa Carambola L.) Against The Bacteria Sthapyloccocus Epidermidi - Dewi Rahayu Utami; Gigih Kenanga Sari; Mingle A Pistanty (Pratama Medika : Jurnal Kesehatan, 2023)
Facial wash or what is usually called facial cleansing soap is the first step to preventing acne (Movita, 2013). This research aims to formulate a facial wash preparation of sweet starfruit leaf extract (Averrhoa carambola L.) with good physical quality evaluation and the potential to inhibit the growth of Staphylococcus epidermidis bacteria. Sweet starfruit leaf powder (Averrhoa carmbola L.) was extracted using the maceration method and with 70% ethanol solvent. The resulting thick extract is tested for chemical content, ethanol free and specific gravity of the extract. Next, an evaluation of the preparation was carried out and an antibacterial activity test was carried out on a facial wash preparation of sweet star fruit leaf extract (Averrhoa carambola L.) with an extract concentration of FI 30%, FII 40%, FIII 50%, using the diffusion method, paper discs, Mueller Hinton Agar media. The results of this research show that starfruit leaf extract (Averrhoa carmbola L.) can be made into a good facial wash preparation and contains alkaloids, flavonoids, saponins, tannins and triterpenoids, which can act as antibacterials. In facial wash preparations, sweet starfruit leaf extract (Averrhoa carmbola L.) produces good physical quality and can inhibit Staphylococcus epidermidi bacteria at FI of 13.503mm±0.580, FII of 38.026mm±4.34 and FIII of 42.51mm±3.178. This shows that the higher the concentration of sweet starfruit leaf extract, the higher the inhibitory power produced